Eksperimentasi Pembelajaran Matematika dengan Menggunakan Model Pembelajaran Kooperatif Tipe Student Tems and Division (STAD) dan Think Pair Share (TPS) terhadap Prestasi Belajar Siswa Ditinjau dari Kemampuan Berpikir Kreatif pada Siswa Kelas VIII SMP Muhammadiyah 1 Kartasura Tahun Ajaran 2016/2017 - Rohmawati, Atika; , Sri Rejeki, M.Pd, M.Sc (2017)
The aim of this study is to find out: (1) the different effects of Student Teams Achievement Division (STAD) and Think Pair Share (TPS) learning models on students' mathematics learning achievement, (2) the different effects of students' creative thinking ability on students' mathematics learning achievement, (3) the effects of interaction between learning models and students' creative thinking ability on students' mathematics learning achievment. This is a quantitative research with a quasi-experimental design. The population of this study is all students of 8th grade at SMP Muhammadiyah 1 Kartasura, and the sample are the students of VIIIB and VIIIC. The data collection techniques used in this study are test and documentation. The data were analyzed using analysis of variance of two different cells with 5% level of significance. Based on the data analysis, it can be concluded that: (1) there are different effects of Student Teams Achievement Division (STAD) and Think Pair Share (TPS) learning models on students' mathematics learning achievement. Student Teams Achievement Division (STAD) learning model affected better than Think Pair Share (TPS) learning model on students' mathematics learning achievement. (2) there are different effects of levels of creative thinking ability on students' mathematics learning achievement. Students with high level of creative thinking ability performed better than those with moderate and low level creative thinking ability. Moreover, students with moderate level of creative thinking ability performed better than those with low level of creative thinking ability. (3) there is no effect of interaction between learning models and students' creative thinking ability on students' mathematics learning achievement.